Tourism - Following the Traces of Past Worlds - Krzymowska-Kostrowicka, Alicja (Turyzm/Tourism, 2005)
The article discusses Issues shared by tourism and the historical anthropology of culture. Its aim is to draw attention to hidden meanings in the spiritual and material traces of the past. Following a short introduction discussing the origins and cultural evolution of humanity, the author passes on to the following issues: how did the evolution of selfperception progress; how was the surrounding world perceived and interpreted: what was the role of caves and labyrinths: how has the spirit of place been perceived; how significant to tourism are 'traces of the past and the ability to read them?